Enhanced Nerve Regeneration by Bionic Conductive Nerve Scaffold Under Electrical Stimulation - Liu, Zhenhui; Liu, Yanshi; Yushan, Maimaiaili; Yusufu, Aihemaitijiang (Frontiers in Neuroscience, 2022)
Repair of peripheral nerve defect (PND) with poor prognosis was hard to deal with. Neural conduit applied to nerve defect at present could not achieve the effect of autologous nerve transplantation. We prepared bionic conductive neural scaffolds to provide a new strategy for the treatment of peripheral nerve defects. The high aligned poly (l-lactic acid) (PLLA) fiber mat and the multi-microchannel conductive scaffolds were combined into bionic conductive nerve scaffolds which were implanted into the sciatic nerve defect of rats. The experimental animals were divided into scaffold group (S), scaffold with electrical stimulation group (S&E) and autologous nerve transplantation group (AT). The regenerative effect of bionic conductive nerve scaffolds was analyzed. Compared with aligned PLLA fiber mat, highly aligned fiber mat had a higher fiber orientation and did not change the tensile strength, Young's modulus, degradation rate, elongation at break of the fiber membrane and biocompatibility. The bionic conductive nerve scaffolds were well matched with rat sciatic nerve. The evaluations of sciatic nerve in group S&E were close to those in group AT, and better than those in group S. Immunohistochemical results showed that the expression levels of Neurofilament heavy polypeptide (NF-H) and Protein S100-B (S 100-β) in group S&E were higher than those in group S, and the expression levels of Low-density lipoprotein receptor-related protein 4 (LRP4), Mitogen-activated protein kinase (MAPK) p38, Extracellular signal-regulated kinase (ERK) and Mitogen-activated protein kinase kinase (MEK) in group AT were higher than those in group S. Bionic conductive nerve scaffolds combined with electrical stimulation (ES) could enhance peripheral nerve regeneration and achieve satisfactory nerve regeneration close autologous nerve grafts. ERK, p38MAPK, MEK and LRP4 may be involved in peripheral nerve regeneration under electrical stimulation.